BCS glossary of computing and ICT (Swindon : British Informatics Society, 2008)
A glossary of computing designed to support those taking computer courses or courses where computers are used, including GCSE, A-Level, ECDL and 14-19 Diplomas in Functional Skills, in schools and Further Education colleges. It helps the reader build up his knowledge and understanding of computing.
Figures and tables; Introduction; How to use this Glossary; Part A -- How computer systems are used; Section 1: General computing terms; Section 2: Using your computer; Section 3: Word processing and text manipulation; Section 4: Graphics, design and digital imaging; Section 5: Sound; Section 6: User interface and documentation; Section 7: Commercial data processing (DP); Section 8: Spreadsheets; Section 9: Data handling and information retrieval; Section 10: Modelling and simulation; Section 11: Internet; Section 12: Networking; Section 13: Control and monitoring. Section 14: Artificial or machine intelligenceSection 15: Computer personnel; Section 16: Computer security, abuse and related law; Section 17: Specialised computer applications; Section 18: Types of computer; Section 19: Input; Section 20: Memory; Section 21: Output; Section 22: Communications components; Section 23: Systems design and life cycle; Section 24: Describing systems; Section 25: Programming concepts; Section 26: Programming (flow of execution); Section 27: Programming (subprograms); Section 28: Program syntax; Section 29: Describing programs. Section 30: Testing and running programsSection 31: Programming languages; Section 32: Data representation; Section 33: Numeric data representation; Section 34: Managing data files; Section 35: Systems software; Section 36: Machine architecture; Section 37: Interfaces and buses; Section 38: Physical components; Section 39: Communications technology; Section 40: Truth tables and logic gates; Section 41: Acronyms and abbreviations; Section 42: Units; Section 43: Filenames and filename extensions; Section 44: Geographic domain identifiers; Section 45: ASCII character codes; Index.
British Computer Society glossary of computing and ICT Glossary of computing and ICT Glossary of computing and information and communications technology
Includes bibliographical references and index.
Keywords: COMPUTERS -- DICTIONARIES